Desenvolvimento de locos de microssatélites para Trema micrantha - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
Trema micrantha (L.) Blume is a native forest species of Brazil, a pioneer and rapid growth. The species has a wide range of benefits, from use as raw material to soil conservation and recovery of normal forest conditions. The wood is used for light buildings and as firewood. There has been fragmentation of populations of tree species in the Amazon due to deforestation for agriculture or by extraction. This study aimed to develop specific microsatellite primers for Trema micrantha species and characterize the genetic diversity of a natural population of this species. Thus, we developed microsatellite loci isolated from a genomic library enriched with these markers, which were used to characterize a population with T. micrantha of individuals, coming from Manaus, Amazonas. Were randomly identified in the study area, 30 trees to represent the population. The study provided information on the genetic diversity of the population based on estimates of allelic and genotypic frequencies, was estimating the magnitude and distribution of genetic variability within the sampling area. From the developed genomic library was obtained and sequenced a total of 120 colonies. From the colonies were identified 41 designed and selected microsatellite, which is 34.17% enrichment. Among these, 11 microsatellites showed amplification products to 60° C, 6 (54.5%) monomorphic for the group of subjects studied. The expected heterozygosity values (He) ranged from 0.171 to 0.717, with an average of 0.438. The observed heterozygosity (Ho) ranged from 0.133 to 0.308, with an average of 0.196. The Tmi04, Tmi28 and Tmi36 markers shown to be moderately informative. Microsatellite markers synthesized in this work can be used for polymorphism analysis of individuals of T. micrantha other genetic studies. The genotypes analyzed showed an excess of homozygosity in most loci, suggesting strong inbreeding in the population studied.
Keywords: Cannabaceae; Molecular marker; Genetic diversity; Crindiúva; Marcador molecular; Diversidade genética; CIÊNCIAS AGRÁRIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL